Sandwiching intermetallic Pt3Fe and ionomer with porous N-doped carbon layers for oxygen reduction reaction - Xiaoqing Cao; Hongyu Guo; Ying Han; Menggang Li; Changshuai Shang; Rui Zhao; Qizheng Huang; Ming Li; Qinghua Zhang; Fan Lv; Hao Tan; Zhengyi Qian; et al. (Nature Communications)
Abstract Proton exchange membrane fuel cells show great potential as power source for automobiles, yet are now facing technological challenges of low efficiency in the cathodic oxygen reduction reaction and severe degradation from Nafion ionomers. Herein, we report the design and construction of a core/shell nanoparticle, composing of Pt3Fe intermetallic nanoparticle as core and atomically-thin porous N-doped carbon layer as shell, to alleviate Nafion ionomer poisoning and local oxygen transport at the interfaces, thereby improving the performance of membrane electrode assemblies. Combining electrochemical, spectroscopic and calculation results verify that the sandwiching carbon layer can effectively prevent surface Pt active sites from poisoning by ionomers. Moreover, this deliberate design facilitates a more homogeneous distribution of ionomers in catalyst layer, and drives a H2-air fuel cell peak power density up to 1.0 W cm-2. Due to the configuration-induced strong Fe-N coordination, our unique catalyst efficiently preserves transition metals and consequently delivers a notable fuel cell durability at a constant potential of 0.5 V for 100 h.